ORCID education: a departmental approach. Issue 1 (15th February 2021) - Droog, Alissa; Bredahl, Laura M.
Abstract : Purpose: This paper aims to provide a case study of an ORCID promotion at the University of Waterloo School of Optometry and Vision Science, providing context for the importance of education in ORCID outreach. Design/methodology/approach: The three-month ORCID promotion used workshops and individual appointments to educate faculty about ORCID, identity management systems and research impact and scholarly communications. Findings: A targeted and personal approach to ORCID promotion focused on education about why you might use this author disambiguation system resulted in 80% of the faculty within the School of Optometry and Vision Science signing up for, or using ORCID. Scaling an ORCID implementation to a larger group would likely benefit from a dedicated project group, and integration with existing institutional systems such as a requirement of an ORCID for internal grant applications. Originality/value: Although time consuming, this small-scale ORCID promotion with one department reveals that a departmental approach to ORCID education may lead to larger conversations about scholarly communications and a stronger relationship between faculty and the library.